Oestrus characteristics in Jakhrana goats - GOEL, A K; AGRAWAL, K P (The Indian Journal of Animal Reproduction, 2023)
Study on oestrus characteristics ( oestrus symptoms and duration) at different physiological stages was conducted in two hundred eighty two (pubertal: 90. post-pubertal: 20, and post-partum: 172) Jakhrana goats, maintained under semi-intensive system of management at experimental sheds of this institute. Oestrus detection was carried out at 6-12 hours interval. Behavioural oestrus symptoms (moderate) were observed at puberty while goats at first post-partum oestrus expressed behavioural oestrus of weak intensity. Post-pubertal (nulliparous and parous) goats exhibite typical oestrus symptoms. Oestrus duration in pubertal goats averaged 27.97± 1.43 hr (range: 12 to 60 hr) and majority of goats remained in oestrus for 24 to 36 hr. Type and season of birth did not influence its duration (P>0.05). In post-pubertal goats oestrus duration averaged 29.28±0.98 hr (nulliparous: 28.4<h: 1.26. parous: 30.26± 1.53 hr) and majority of goats remained in oestrus for 19 to 36 hr. Incidence of short ( 6- 18 hr). long (37-48 hr) and very long (>48 hr) oestruses was also noticed. In post-partum goats, first oestrus averaged 25.25±0.88 hr(range: 12 to 60 hr) and majority (64%) of goats remained in oestrus for 24 to 36 hr. Goats kidded during Dec.-Jan. had highest (28.50± 1.77 hr) and those kidded during April had lowest (17.14±2.42 hr) post-partum oestrus duration (P<0.05). The difference in oestrus duration among different physiological stages was statistically non-significant (P>0.05) and majority of them remained in oestrus for 24 to 36 hr. Infonnation on oestrus symptoms and duration will help to mate Jakharana goats at proper time for optimum flock fertility.